Case Report: Two cases of long-term survival in advanced pancreatic cancer patients following treatment with KRAS G12C inhibitors - Aslani, Saeed; McKay, Owen; Lipton, Lara; Ganju, Vinod; Croagh, Daniel (Frontiers in Oncology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy with a dismal prognosis. Molecular profiling to improve the diagnosis and management of PDAC holds promise for informing more targeted therapies such as Kirsten rat sarcoma viral oncogene homologue (KRAS) G12C inhibition to deliver better outcomes for these patients. In this report, we present two patients with advanced PDAC with KRAS G12C mutations who achieved remarkable disease control and prolonged survival following treatment with the KRAS G12C inhibitor D1553 (garsorasib). Case 1, a 74-year-old woman with recurrent PDAC post-surgical resection and chemotherapy, exhibited a significant biochemical and radiologic response upon initiation of targeted therapy. Case 2, a 75-year-old woman initially treated with Folinic acid, fluorouracil, irinotecan and oxaliplatin (FOLFIRINOX) and stereotactic body radiotherapy (SBRT), demonstrated sustained disease stability for over three years on KRAS G12C inhibitor therapy. Both patients maintained excellent performance status with minimal treatment-related toxicity. These cases underscore the potential of KRAS-directed therapies in PDAC and illustrate the importance of molecular profiling in identifying eligible patients. The findings support further investigation into the durability of KRAS G12C inhibition, resistance mechanisms, and combination treatment strategies to optimize patient outcomes.